Thrombocytosis with acquired von Willebrand disease in an adolescent with sickle cell disease - Marianne E. M. Yee; Glaivy Batsuli; Satheesh Chonat; Sunita Park (Clinical Case Reports, 2021)
Abstract Thrombocytosis is common in sickle cell disease and may contribute to vaso‐occlusion. Hydroxyurea treats extreme thrombocytosis. Acquired von Willebrand disease should be considered prior to aspirin therapy.